Research on the Collaborative Operational Mode and Key Technologies of Manned/Unmanned Aerial Vehicles - Sun Shengzhi, Meng Chunning, Hou Yan, Cai Xiaobin (Hangkong bingqi, 2021)
With the continuous progress of military technology, unmanned aerial vehicles have been more and more widely used in military operation and play an increasingly important role. The collaborative operational mode of manned/unmanned aerial vehicles will surely become an important operational mode in the future. According to the application of unmanned aerial vehicles in the collaborative operational system, the manned/unmanned aerial vehicles collaborative operational architecture is constructed, and the passive centralized, semi-active distributed and resident distributed collaborative operational modes of manned/unmanned aerial vehicles are studied, and key technologies for supporting future manned/unmanned aerial vehicles collaborative operation are proposed. It is of great practical and theoretical significance to enhance the capability of collaborative operation.